A critical discourse analysis of the representation of Iraqi Kurds and shites in Time and Newsweek before and after the us-led invasion - Mustafa, Manar Munjid (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This research is carried out to examine the change in the representation of Iraqi Kurds and Shiites before and after the US-led invasion though a critical discourse analysis of forty TIME and Newsweek articles published during November, 2002-March, 2003 and January-May, 2007. The reason for choosing these time periods is that before the invasion both Iraqi Kurds and Shiites were seen as United States allies. However, anti- US Shiite groups emerged after the invasion while Kurds remained loyal to the United States. The study is limited to using Fairclough's three-stage analysis. Firstly in the Description stage, vocabulary, ergativity and implicature analyses are used to examine headlines and discourse features, specifically, naming choices, lexical choices, overcompleteness and voice are used to examine full-text articles. The second stage of the analysis, namely Interpretation, establishes a link between the text and the discourse practice, and finally, the third stage Explanation, deals with explaining the relationship between the interaction and social context. The comparative analysis shows that both newsmagazines represented both Iraqi Kurds and Shiites positively before the invasion. However, the representation of Iraqi Shiites changed substantially in the examined period after the invasion. By observing the political context during both periods, the study reveals that an important factor controlling the representation of both groups was the nature of the United States' relation to both Iraqi Kurds and Shiites during the studied periods.